SUBSTITUSI TERIGU DENGAN TEPUNG KEDELAI DAN PENAMBAHAN TEPUNG KACANG HIJAU TERHADAP SIFAT ORGANOLEPTIK MUFFIN - Liza Choerunnisa (2020)
At present there are still many nutritional problems experienced by school-age children. Many school children still have poor eating habits such as the consumption of unhealthy foods and the tendency to consume instant and fast food. These habits can cause lack of fiber and protein intake in school-age children. Consuming food sources for fiber and protein can prevent these problems. Muffins are generally made from wheat flour, which is an imported ingredients that contains gluten. In this study, wheat flour was substituted by soy flour with an addition of green bean flour. This study aimed to determine the organoleptic properties of soy flour muffin added with mung bean flour. This study uses an Experimental method with 3 treatments of flour, soy flour, andmung bean flour, 40:60:20, 20:80:20, 0:100:20. The muffins were then tested for organoleptic properties. The method used was a hedonic test on 30 semi-trained panelists. The hedonic tests were performed to analyze the preference for color, taste, aroma and texture. The Selected formula is F1 with flour 40 g, soy flour 60 g and mung bean flour 20 g. The formula has an estimated protein content of 3,8 g and 0,9 g fiber per serving. As a suggestion, the appearance and uniformity aspects for the shape of the muffin should be considered more. Nutritional analysis needs to be done to get more accurate results.